ANALYSIS OF FINANCIAL MANAGEMENT AND TRANSPARENCY ON THE PERFORMANCE OF THE JOINT VILLAGE-OWNED ENTERPRISE OF SINGOROJO, KENDAL REGENCY, WITH PUBLIC TRUST AS AN INTERVENING VARIABLE - Nur Yasin; Sunarto Sunarto (Journal of Industrial Engineering & Management Research, 2026)
The performance of Village-Owned Joint Enterprises (BUMKDesma) is influenced by several factors, including financial management, transparency, and public trust. This study aims to examine the effects of financial management and transparency on the performance of BUMDesma Singorojo, Kendal Regency, by incorporating public trust as an intervening variable. A quantitative approach was employed using primary data collected through questionaires distributed to 155 respondents, consisting of customers, business partners, and village heads in Singorojo District. The data were analyzed using multiple linear regression, while the mediating effect of public trust was examined through the Sobel test.The findings indicate that financial management has a positive and significant effect on both public trust and BUMDesma performance. Transparency also has a positive and significant effect on public trust; however, it does not significantly influence BUMDesma performance. Furthermore, public trust has a positive and significant impact on organizational performance. The mediation analysis reveals that public trust successfully mediates the relationship between financial management and BUMDesma performance but fails to mediate the relationship between transparency and organizational performance.The study highlights that accountable financial management plays a strategic role in improFing BUMDesma performance, both directly and indirectly through strengthening public trust. Therefore, BUMDesma managers are encouraged to enSance financial management practices, reinforce accountability, and maintain public trust to support organizational sustainability and improve overall performance.